Buprenorphine treatment receipt characteristics and retention among people who inject drugs at Integrated Care Centers in India. (1st May 2023) - Ganapathi, Lakshmi; McFall, Allison M.; Greco, Kimberly F.; Srikrishnan, Aylur K.; Kumar, Muniratnam Suresh; Mayer, Kenneth H.; O'Cleirigh, Conall; Mehta, Shruti H.; Lucas, Gregory M.; Solomon, Sunil S.
Abstract: Background: India is facing overlapping opioid injection and HIV epidemics among people who inject drugs (PWID) in several cities. Integrated Care Centers (ICCs) provide single-venue HIV and substance use services to PWID. We evaluated PWID engagement in daily observed buprenorphine treatment at 7 ICCs to inform interventions. Methods: We analyzed 1-year follow-up data for PWID initiating buprenorphine between 1 January – 31 December 2018, evaluating receipt frequency, treatment interruptions (no buprenorphine receipt for 60 consecutive days with subsequent re-engagement), and drop-out (no buprenorphine receipt for 60 consecutive days without re-engagement). Using descriptive statistics, we explored differences between ICCs in the opioid-endemic Northeast region and ICCs in the emerging opioid epidemic North/Central region. We used a multivariable logistic regression model to determine predictors of treatment drop-out by 6 months. Results: 1312 PWID initiated buprenorphine (76% North/Central ICCs vs. 24% Northeast ICCs). 31% of PWID in North/Central, and 25% in Northeast ICCs experienced ≥ 1 treatment interruption in 1 year. Over 6 months, 48% of PWID in North/Central vs. 60% in Northeast ICCs received buprenorphine ≤ 2 times/week (p < 0.0001). A third of PWID in North/Central vs. half in Northeast ICCs experienced treatment drop-out by 6 months (p < 0.001). In the multivariable model, living in Northeast cities was associated with increased odds of drop-out while counseling receipt was associated with decreased odds. Conclusions: Retention among PWID initiating buprenorphine at ICCs was comparable to global reports. However, regional heterogeneity in retention, and low daily buprenorphine receipt suggest patient-centered interventions adapted to regional contexts are urgently needed. Highlights: 62% of PWID initiating buprenorphine at ICCs were retained in treatment at 6 months. Daily buprenorphine receipt was low, with 50% of PWID receiving medications on average at a frequency of ≤ 2 times a week. 30% of PWID experienced ≥ 1 treatment interruption. Living in Northeast cities was associated with increased odds of treatment drop-out by 6 months. Receipt of counseling was associated with decreased odds of treatment drop-out by 6 months.